The Manila Declaration on Migration and Health: commentary of the Association of Pacific Rim Universities Global Health Program - Mellissa Withers; Heather Wipfli; Marc Schenker; Tasfia Jahangir; Teodoro Herbosa; Jorge Tigno (BMC, 2020)
Abstract Background Migration has played, and continues to play, an important role in shaping our global economy. As of 2017, there were 258 million international migrants worldwide, over 100 million of whom came from the Asia-Pacific region. Migration is increasingly recognized as a social determinant of health, as migrants often experience vulnerabilities that make them susceptible to a range of negative health outcomes. Addressing the health and human rights concerns of migrants requires concerted and global efforts from many stakeholders, including universities. Methods The Global Health Program of the Association of Pacific Rim Universities (APRU), a non-profit network of more than 50 universities in the region, is an example of an avenue to foster research, innovation, collaborative engagement, and large-scale advocacy around migration and health. In 2017, a special half-day workshop was held in Manila, convening 167 participants from 10 economies and 21 disciplines. The goal of the workshop was to delineate the role of universities in promoting migrant health and well-being. The global health experts from a diverse set of backgrounds collaboratively developed a policy statement to be used to better address migrant health and human rights. The objective of this paper is to disseminate the policy statement, highlighted specific action items that universities can take to protect and promote migrant health. Results The Manila Declaration on Migration and Health highlights that universities must ensure that their campuses are safe, supportive, and empowering environments for all migrants and their families. Universities are also urged to capitalize on their educational and research expertise to generate data on migrant experiences and communicate this research to policymakers. Conclusions This commentary highlights how institutions of higher education can serve as powerful avenues for promoting migrant health and human rights. Universities can play a vital role in building awareness and sensitivity to migrant challenges and needs, as well as helping to develop policy frameworks appropriate to their diverse contexts to guide, promote, and reinforce commitment to migrant rights and health. Universities should also ensure that their campuses are safe, supportive, and empowering environments for all migrants and their families.